Pesan Kritik Sosial Guzman Sige - Suryana Khairuddin (Bandung Conference Series: Communication Management, 2024)
Abstract. Stand-up comedy is rapidly growing in popularity in Indonesia, with shows like Stand Up Comedy Indonesia attracting considerable public interest. The appeal of stand-up comedy lies in its humorous approach, which makes complex messages more accessible and relatable. It often reflects societal values and realities, offering a comedic perspective on social issues. One prominent figure in this genre is Guzman Sige, a notable comedian from Bandung, who has significantly influenced the city's stand-up comedy scene. Sige's performances, including those in the Sebelah Mata Stand Up Comedy Show Bandung, frequently incorporate social criticism. This research, titled "Guzman Sige's Message of Social Criticism: Content Analysis of Sebelah Mata Stand Up Comedy Show Bandung Material," employs a quantitative descriptive method and a quantitative content analysis approach. The study aims to uncover the extent and nature of social criticism present in Sige's material. The findings indicate that Sige's work contains substantial social critique, highlighting various issues within Bandung's social landscape. This underscores the role of stand-up comedy as both an entertainment medium and a platform for social commentary. Abstrak. Stand Up Comedy berkembang pesat di Indonesia, dengan acara seperti Stand Up Comedy Indonesia yang semakin populer di kalangan masyarakat. Daya tarik utamanya terletak pada pendekatan humoris yang membuat pesan-pesan kompleks lebih mudah dipahami dan diterima. Stand Up Comedy sering kali mencerminkan nilai-nilai dan realitas sosial, menawarkan sudut pandang komedi terhadap isu-isu sosial. Salah satu tokoh penting dalam genre ini adalah Guzman Sige, seorang komedian terkenal dari Bandung yang telah mempengaruhi perkembangan budaya Stand Up Comedy di kota tersebut. Penampilan Sige, termasuk dalam acara Sebelah Mata Stand Up Comedy Show Bandung, sering kali menyertakan kritik sosial. Penelitian ini berjudul "Pesan Kritik Sosial Guzman Sige: Analisis Konten Materi Sebelah Mata Stand Up Comedy Show Bandung" menggunakan metode deskriptif kuantitatif dan pendekatan analisis konten kuantitatif. Tujuan penelitian ini adalah untuk mengungkap sejauh mana dan bagaimana kritik sosial muncul dalam materi Sige. Temuan penelitian menunjukkan bahwa karya Sige memang mengandung kritik sosial yang signifikan, menyoroti berbagai masalah dalam lanskap sosial Bandung. Hal ini menegaskan peran Stand Up Comedy sebagai media yang kuat untuk hiburan sekaligus komentar sosial.